(( دراسة تجريبية للخصائص الفيزياكيميائية والهيدروديناميكية والميكانيكية لتربتين نمطيتين من أتربة جمهورية مصر العربية )) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
In this research work, conducted in Egypt between December 2006 and April 2007, physiochemical, hydrodynamic and mechanical characteristics were evaluated for two prominent Egyptian agricultural soils. These are the ancient delta clayey soil (Itai El Baroud, western Nile Delta) and the newly reclaimed sandy soil of the Egyptian desert (West Nubaria). They represent the most important agricultural soil types in the country. Results showed major discrepancies between the two soils. Nubaria soils contained merely about 1.0% clay, whereas the Delta soil had about 54% clay. This was reflected in the moisture-retention  characteristic curves, as well as the hydrodynamic functions, soil porosity, hydraulic conductivity, susceptibility to densification and compression,. Also, the two soils displayed wide differences in their chemical properties أنجز هذا البحث في جمهورية مصر العربية بين شهر كانون الأول 2006م  وشهر آذار2007م  حيث تمّ فيه تحديد الخواص الفيزياكيميائية  والهيدروديناميكية والميكانيكية  لتربتين واسعتي الانتشارمن الأتربة الزراعية المصرية هما الأتربة الطينية القديمة للدلتا  (منطقة إيتاي  البارود  في دلتا النيل الغربية ), و الأتربة الرملية المستصلحة حديثا من الرمال  المصرية (غربي منطقة النوبرية )،و اللتان تمثلان أهم الأتربة النمطية  الزراعية  في مصر. لقد بينت النتائج تباينا واسعا جدا  بين النوعين من التربة ,حيث تميزت تربة النوبرية  بنسبة ضعيفة جدا من الطين بحدود 1% ,في حين وصلت نسبة الطين  في تربة الدلتا إلى حوالي 54% . لقد انعكس هذا التباين على مواصفات منحنيات الشد الرطوبي , وعلى التوابع  الهيدروديناميكية للتربة , وكذللك على مسامية التربة وتوصيلها الهيدروليكي وقابليتها للتكثف وللانضغاط . كذلك فقد أبدت التربتان تباينا واسعا في خصائصهما الكيميائية .